Assessing the level of innovation of Poland from the perspective of regions between 2010 and 2020 - Jarosław Brodny; Magdalena Tutak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The growing and expanding zone of the free-market economy results in increasing competition in the global market, which leads companies to seek and implement solutions that will give them a competitive advantage. The authorities of countries and regions are also increasingly involved in this process, seeing it as an opportunity to develop and build a knowledge-based economy. One of the main factors improving competitiveness and providing opportunities for development is innovation, particularly developed at the local level. For this reason, activities that support research and development of innovation at the regional level are increasingly appreciated and gain greater importance. This article refers to regional innovation in Poland by analyzing its level between 2010 and 2020. The basis of the analysis was 15 selected indicators characterizing three dimensions related to the innovative development of regions, namely innovative capacity, innovative position, and economic development. This assessment was regarded as a multi-criteria problem, for which the CODAS method was used. Its application made it possible to achieve the main objective of this paper, which was to determine the level of innovation of studied regions and, on this basis, to create their ranking. In addition, the evaluation of the level of innovation of the regions for each of the analyzed dimensions was also carried out, and the relationship between the level of economic development and the capacity and innovative position of the regions was specified. The measure for evaluating the level of innovation, for each case studied, was the value of the Hi index, taken as a synthetic measure of regional innovation. The results show that the level of innovation for the regions in Poland varies widely as a function of time as well as the location of these regions. Differences in the dynamics of change and different levels of development of the analyzed dimensions characterizing innovation are evident. The results provide new knowledge in the field of regional development and should be used when creating a regional development strategy for individual regions, Poland, and the EU.
Keywords: 650; CODAS method; economic growth; innovation; open innovation; regional development